Synthesis And Characterization Of New Series Of Liquid Crystalline Compounds Containing Azobenzene And Bisazobenzene Moieties - Abubakar Salisu, Abdulsalam (2009)

(untitled)
New molecular structures based on azobenzene and bisazobenzene mesogenic units, which can support mesophase were prepared, in particular four different types of liquid crystalline materials have been synthesized and characterized, following the general criteria. All materials were characterized by spectroscopic methods (FT-IR, NMR, MS and CHNS analyses) and the liquid crystalline properties were investigated using differential scanning colorimetry (DSC), optical polarizing microscopy (OPM) and, X-ray diffraction. The presence of smectic A mesophase was confirmed by the textures and X-ray diffraction studies (XRD). The calamitic liquid crystals (rod-shaped) compounds were generally synthesized via diazotization of primary aromatic amine, coupling with phenol and subsequent etherification of phenol with ten fold excess of an appropriate α,ω-dibromoalkane which was further etherified in methanol to give the final compounds, giving rise to a typical features of calamitic liquid crystals (rod-shaped) compounds. Four of the liquid crystalline compounds containing azobenzene moiety denoted as AZOn series, exhibited enantiotropic smectic A phase AZO3-AZO6 (C3-C6) while, compound AZO8 (C8) show monotropic smectic A phase. The liquid crystalline trimer (AZOTn series) containing azobenzene with a short acetyl mesogenic group and a biphenyl as central mesogenic core were prepared by employing the procedures described for the calamitic mesogenic compounds above. The final compound was produced by etherification of the 4`4-hydroxybiphenyl with two-fold mole ratio of 1-bromoalky-(4-phenylazo)acetophenone. Compound with C5 polymethylene flexible alkyl spacer (AZOT5) exhibited enantiotropic nematic and smectic A liquid crystalline properties. While the compound with C6 polymethylene flexible alkyl spacer showed an enantiotropic nematic phase, the (AZOT6) exhibited the higher values of melting and clearing temperatures. The calamitic bisazobenzene liquid crystal series (BAn series) were synthesized from 4-phenylazoaniline as mentioned above. All the compounds were found to show enantiotropic mesophase behavior and the presence of enantiotropic behavior throughout the series might be connected to the bisazobezene core and the terminal groups that extend the molecules along their molecular axes which, increase thermal stability of the mesophases and anisotropy of molecular polarizability. The photoisomerization experiment indicates a decrease in intensities of the absorption bands for compound BA4 (BAn series). These show that the structure of the compounds does not have significant effect on the photoisomerization rate. This group of compounds have potential application in photonics more specifically, in reversible optical data storage, optical switching devices, optical computing and integrated optical devices for communication. The final series of compound 4-propyloxy-[4-biphenyloxyalkyl]-4`-(4-phenylazo)azobenzene for the dimer containing bisazobenzene mesogenic moiety and alkoxybiphenyl linked by flexible spacers (BAOnO.3 series) was prepared by reacting the 4-propyloxy-4-hydroxybiphenyl with 1-bromoalkyloxy-4`-(4-phenylazo)azobenzene. The synthesized compounds exhibited enantiotropic phase with dimer containing propyl, butyl and octyl as flexible alkyl spacers showing SmA and those with pentyl and hexyl spacers exhibited SmA and SmC phases respectively. The stability of the smectic layer depends on the spacer length for the compounds studied.